(untitled) (Bangladesh Journal of Otorhinolaryngology, 2012)
Objective: To study the clinical, radiological along with the management outcome of Eagles syndrome. Study design: Prospective. Setting: Department of Otolaryngology - Head and Neck Surgery, Ibn Sina Medical College Hospital and Ibn Sina Hospital, Dhaka, Bangladesh. Methods: This study included twenty patients with Eagles syndrome presented to Ibn Sina Medical College, Dhaka and Ibn Sina Hospital, Dhaka, from April 2009 to January 2012. The data of each patient included age, sex, presenting symptoms and signs, radiological investigations, operative notes and state at follow up. Results: Out of twenty patients, twelve (60%) were female and eight (40%) were male. Maximum nine patients (45%) belonged to the fourth decade. The mean age of presentation was 42.5 years. Maximum patients (100%) presented with pain and foreign body sensation throat. In all cases, a sharp prick was felt and pain was increased on palpation of the upper part of tonsillar fossa. In fourteen cases (70%) elongated styloid process was bilateral and in six cases (30%) it was unilateral. X-ray Townes view, lateral view of skull base & neck and CT scan were excellent diagnostic tools as well as to measure the length of styloid process. In all cases partial styloidectomy was done via intra-oral approach. Eighteen patients (90%) were symptom free in three months follow up. Two patients (10%) had pain in throat and other symptoms even after three months follow up and were treated with oral carbamazepine. Conclusion: Eagles syndrome associated with elongated styloid process is a rare clinical entity. The diagnosis can easily be made with clinical examination and radiological findings. Awareness of this syndrome is important to all ENT practitioners and related specialty involved in diagnosis and treatment of Head and Neck pain. DOI: http://dx.doi.org/10.3329/bjo.v18i2.12006 Bangladesh J Otorhinolaryngol 2012; 18(2): 149-155